ANALISA KEPASTIAN HUKUM JAMINAN FIDUSIA DALAM PERJANJIAN KREDIT TERKAIT PENGALIHAN OBJEK JAMIAN FIDUSIA TANPA PERSETUJUAN KREDITUR - Aneke Jeaned Von Bulow; Iran Sahril; Dedy A. Prasetyo (Bajang Institute, 2025)
The fiduciary security system is an essential instrument in financing but often faces challenges, particularly regarding the transfer of secured objects without the creditor's consent. This issue can jeopardize the creditor's right to execute the secured asset in case of debtor default. Article 36 of Law No. 42 of 1999 aims to protect creditors by prohibiting unauthorized transfers, although its implementation often encounters legal, technical, and administrative obstacles, necessitating further study. This research aims to analyze the implementation of Article 36 of Law Number 42 of 1999 on Fiduciary Security in prohibiting the transfer of fiduciary objects without creditor approval and to examine legal certainty for creditors in the context of violations of this provision. Using the theory of security and legal certainty as analytical frameworks, this study evaluates three Supreme Court decisions: Number 109 K/PID.SUS/2019, Number 2526 K/Pid.Sus/2024, and Number 278/Pid.Sus/2017/PT SMG.The findings reveal that the implementation of Article 36 not only normatively prohibits the transfer of fiduciary objects without creditor consent but also provides legal protection through criminal sanctions for violations. In practice, court flexibility is evident in considering the good faith of debtors who resolve disputes amicably, as seen in Decision Number 109 K/PID.SUS/2019. However, in other cases, such as Decisions Number 2526 K/Pid.Sus/2024 and Number 278/Pid.Sus/2017/PT SMG, strict law enforcement remains a priority to uphold creditor rights and prevent misuse of fiduciary objects.This research also highlights the relevance of Article 36 in the digital era. Digitalization of fiduciary documents and the use of tracking technologies such as GPS and blockchain can enhance efficiency and transparency, providing additional protection for creditors. Recommendations include strengthening regulations, adopting technology, and raising public legal awareness to ensure optimal legal protection in the fiduciary system.